Evaluation of the efficacy of commercial and noncommercial tourniquets for extremity hemorrhage control in a perfused cadaver model. Issue 3 (2nd March 2021) - Cremonini, Camilla; Nee, Nadya; Demarest, Matthew; Piccinini, Alice; Minneti, Michael; Canamar, Catherine P.; Benjami, Elizabeth R.; Demetriades, Demetrios; Inaba, Kenji
Abstract : BACKGROUND: Tourniquets are a critical tool in the immediate response to life-threatening extremity hemorrhage; however, the optimal tourniquet type and effectiveness of noncommercial devices remain unclear. Our aim was to evaluate the efficacy of five tourniquets in a perfused-cadaver model. METHODS: This prospective study used a perfused-cadaver model with standardized superficial femoral artery injury bleeding at 700 mL/min. Five tourniquets were tested: combat application tourniquet; rapid application tourniquet system; Stretch, Wrap, And Tuck Tourniquet; an improvised triangle bandage windlass; and a leather belt. Forty-eight medical students underwent a practical hands-on demonstration of each tourniquet. Using a random number generator, they placed the tourniquets on the bleeding cadaver in random order. Time to hemostasis, time to secure devices, estimated blood loss, and difficulty rating were assessed. A one-way repeated measures analysis of variance was used to compare efficacy between the tourniquets in achieving the outcomes. RESULTS: The mean ± SD participant age was 25 ± 2.6 years, and 29 (60%) were male. All but one tourniquet was able to stop bleeding, but the rapid application tourniquet system had a 4% failure rate. Time to hemostasis and estimated blood loss did not differ significantly ( p > 0.05). Stretch, Wrap, And Tuck Tourniquet required the longest time to be secured (47.8 ± 17.0 seconds), whereas the belt was the fastest (15.2 ± 6.5 seconds; p < 0.001). The improvised windlass was rated easiest to learn and apply, with 22 participants (46%) assigning a score of 1. CONCLUSION: Four of five tourniquets evaluated, including both noncommercial devices, effectively achieved hemostasis. A standard leather belt was the fastest to place and was able to stop the bleeding. However, it required continuous pressure to maintain hemostasis. The improvised windlass was as effective as the commercial devices and was the easiest to apply. In an emergency setting where commercial devices are not available, improvised tourniquets may be an effective bridge to definitive care.